P61 Community oxygen prescriptions and DNACPR discussions in stockport; an opportunity to improve end of life care planning?. (15th November 2016) - Morris, C; Parry, S; Holmes, P; Gupta, V
Abstract : Introduction: Many patients who are prescribed home oxygen are symptomatic from progressive, life-limiting disease. The GMC recommends "if cardiac or respiratory arrest is an expected part of the dying process and CPR will not be successful, making and recording an advance decision not to attempt CPR will help to ensure that the patient dies in a dignified and peaceful manner". 1 In addition, patients who are at risk of death or declining are identified on the gold standard framework (GSF) and future care planned according to their wishes. 2 Objectives: To investigate whether patients prescribed oxygen in the community had Do Not Attempt CPR (DNACPR) discussed and recorded; and secondly to investigate the length of time these patients were on oxygen and had DNACPR discussed/recorded prior to death. Methods: Patients who died between January and June 2016 on home oxygen were identified from the Stockport Home Oxygen Service records. The Stockport Health Record (SHR) and GP practices were consulted to find patients' primary diagnoses and DNACPR status. Results: 43 patients (mean age 73.8 ± 1.8) were identified. The overall median (range) length of time on home oxygen was 191 (5–3617) days. 14 (32.6%) had a community DNACPR form present or discussed 60.7 ± 24.4 days (mean ± sem) prior to death. Most common diagnoses were COPD (n = 19), malignancy (n = 14), ILD (n = 5) and other eg CF, PE (n = 3). Results for these groups are shown in Table 1 . Conclusion: Patients are prescribed home oxygen for many reasons and for variable amounts of time. For many the prescription represents a deterioration in their health. In our cohort of patients only 32.6% had DNACPR discussed/present at death, and median survival after initiation of oxygen was only 191 days. References: End of life care: When to consider making a Do Not Attempt CPR (DNACPR) decision. http://www.gmc-uk.org/guidance/ethical_guidance/end_of_life_DNACPR_ decision.asp. Gold Standards Framework. http://www.goldstandardsframework.org.uk/.